Evaluating the effect of cisplatin on drug-tolerant EGFR-mutant lung cancer - Oksanen, Elias (My University, 2026)
Epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) is commonly treated with EGFR tyrosine kinase inhibitors (EGFR-TKIs) as first-line therapy. EGFR-TKIs are initially effective, but resistance eventually develops, often through drug-tolerant persisters (DTPs), a slowly proliferating subpopulation that survives the initial treatment. Preliminary drug screening indicated that cisplatin, a platinum-based chemotherapeutic that induces DNA damage and elevates reactive oxygen species (ROS), is effective against DTPs. The objectives of this study were to confirm cisplatin’s effect on DTPs derived from EGFR-mutant NSCLC cells and to investigate the underlying mechanisms. The sensitivity of EGFR-mutant cell lines to different chemotherapeutics (cisplatin, docetaxel, gemcitabine, and irinotecan) was evaluated in a dose-response assay. The cytotoxic effects against DTPs were assessed using cell viability and live-cell imaging apoptosis assays. Expression of DNA damage response (DDR) proteins was analysed by Western blotting in HCC827 cells, and changes in intracellular ROS levels were measured using flow cytometry. Cisplatin most effectively reduced viability and increased apoptosis in DTPs, although sensitivity varied between cell lines. In DDR-protein analyses, DTPs exhibited lower basal levels of DDR-associated proteins and showed a blunted DDR response to chemotherapeutics, indicating impaired DDR capacity. In turn, fluorescence-based ROS analysis showed that cisplatin did not significantly increase ROS in parental cells or DTPs, suggesting that EGFR-TKI treatment had already maximized ROS or that the probe’s sensitivity was limited. Overall, cisplatin is particularly effective against DTPs, consistent with a more cell-cycle-independent DNA-damaging effect compared with the other chemotherapeutics, rather than through ROS elevation. While further research is required, these findings highlight cisplatin’s potential to eliminate DTPs and prevent the acquisition of drug resistance in EGFR-mutant NSCLC.
Keywords: platinum-based drugs, non-small cell lung cancer, drug-tolerant persisters, DNA damage response